(untitled) (Bangladesh Journal of Botany, 2024)
Effects of dynamic high-pressure micro-fluidization (DHPM) on the physical and chemical properties of carrot juice was investigated in the present study. Carotene content, turbidity, centrifugal sedimentation rate, soluble solids content, color, and particle size and distribution of the samples homogenized with different pressures were evaluated. When compared with the control sample, carotene content, turbidity, suspension stability, centrifugal sedimentation rate, color, and particle size and distribution of the carrot juice showed a significant difference at different pressures. The result indicated that DHPM could improve the physical and chemical properties of carrot juice, such as increased carotene content, stability and affecting color positively resulting in a desirable high-quality juice for the consumer. Bangladesh J. Bot. 53(1): 123-129, 2024 (March)